Сучасні тенденції страхового захисту органічної продукції аграрних виробників - Павленко, Оксана Павлівна; Pavlenko, Oksana (Мукачівський державний університет, 2018)
В статті розглянуто показники ціноутворення органічної продукції аграрного сектору України. Проаналізовано рівень рентабельності органічної і традиційної продукції рослинництва в середньому по Україні. Автором також проведено аналіз показників страхового захисту за видами сільськогосподарських культур органічного виробництва. The article analyzes the level of productivity of organic and traditional crop production in Ukraine. The author also carried out an analysis of indicators of insurance protection by types of organic crops. The level of insurance payments showed that the largest share in payments on the market was occupied by winter canola due to the number of contracts. The growth rate of contracts for agricultural producers' financing programs coincides with the growth rate of the total number of contracts. It is confirmed by the fact that their share in the total number of contracts remained unchanged. Insurance applied to agricultural producers' financing programs was mainly carried with the support of the Agricultural Fund.
Suchasni tendentsii strakhovoho zakhystu orhanichnoi produktsii ahrarnykh vyrobnykiv
Keywords: страховий захист; insurance protection; страхування; insurance; органічна продукція; organic products; аграрне виробництво; agricultural production; страхова сума; insurance sum; страхові виплати; insurance payments; андерайтинг; underwriting